ETIKA PROFESI GURU DALAM MENJAGA KEDISIPLINAN WAKTU MENGAJAR: STUDI KASUS DI SDN X MERANGIN - Herpinah Imel Eka Mulyani; Denia Putri Rizkia; Rega Rahayu; Rose Melia Serly; Iskandar; Retno Wahyu Ningsih; M Ali Basroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of teacher professional ethics in maintaining teaching time discipline at SDN X Merangin. Teacher professional ethics serves as a moral guideline regulating responsibility, integrity, and professional commitment in carrying out educational duties. Discipline in teaching time reflects teacher professionalism and directly affects learning quality. This study used a descriptive qualitative approach with three classroom teachers and one principal as participants. Data were collected through interviews, observations, and documentation, then analyzed using Miles and Huberman’s interactive model. The findings show that teachers at SDN X Merangin strive to maintain punctuality and teaching readiness as forms of professional responsibility and respect for students. Professional ethics is reflected in punctual attendance, lesson preparedness, and honesty in implementing schedules. However, external duties, administrative tasks, and limited supervision still affect time discipline. The study concludes that teacher professional ethics strongly supports the establishment of discipline, responsibility, and professionalism in primary education.